2019
DOI: 10.1016/j.seizure.2018.11.015
|View full text |Cite|
|
Sign up to set email alerts
|

Simultaneous scalp EEG improves seizure lateralization during unilateral intracranial EEG evaluation in temporal lobe epilepsy

Abstract: A B S T R A C TPurpose: To determine if simultaneous bilateral scalp EEG (scEEG) can accurately detect a contralateral seizure onset in patients with unilateral intracranial EEG (IEEG) implantation. Methods: We evaluated 39 seizures from 9 patients with bitemporal epilepsy who underwent simultaneous scEEG and IEEG (SSIEEG). To simulate conditions of unilateral IEEG implantation with a missed contralateral seizure onset, we analyzed the IEEG recording contralateral to the seizure onset (CL-IEEG), in conjunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 37 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…135 Scalp ictal EEG may falsely localize and lateralize focal seizures, 136 especially those arising from mesial and posterior quadrant neocortices 127,137 but may be potentially localized when iEEG is recorded. 138,139 Overall, one Class II study provides low confidence in evidence that more than one-third of patients will experience a change in management after undergoing VEM.…”
Section: Yield Of Inpatient Lt Vemmentioning
confidence: 99%
“…135 Scalp ictal EEG may falsely localize and lateralize focal seizures, 136 especially those arising from mesial and posterior quadrant neocortices 127,137 but may be potentially localized when iEEG is recorded. 138,139 Overall, one Class II study provides low confidence in evidence that more than one-third of patients will experience a change in management after undergoing VEM.…”
Section: Yield Of Inpatient Lt Vemmentioning
confidence: 99%
“…In the first study on 13 patients with focal epilepsy and SSIEEG, the presence of an insufficient latency, absence of congruence in the location, or lack of concordance in the EEG pattern was associated with a lower chance of detecting the seizure onset zone. In a second study, Anthony et al 14 showed that application of the same criteria can accurately detect a contralateral seizure onset in patients with unilateral iEEG implantation and simultaneous bilateral scEEG. Absence of congruence of ictal onset localization was the more sensitive feature than pattern-based or latency-based criteria and SSIEEG, when added to unilateral iEEG, provided better lateralization than the time of onset of clinical manifestations during seizures.…”
Section: Simultaneous Scalp and Ieegmentioning
confidence: 99%
“… 1 In patients with unilateral implantations, it can provide noninvasive coverage of the contralateral hemisphere, partially mitigating the risk of false seizure lateralization. 9 In patients with scalp onsets before stereo EEG onset, it raises a red flag of suboptimal implantation strategy. 4 In patients with seizures induced by potential traumatic effect during electrode implantation, it allows for comparison of their morphology with the previously recorded ictal patterns during the phase I investigation, allowing for correct identification of the patient’s habitual seizures.…”
Section: Commentarymentioning
confidence: 99%